2020
DOI: 10.1063/5.0009045
|View full text |Cite
|
Sign up to set email alerts
|

Microstrip resonator for nonlinearity investigation of thin magnetic films and magnetic frequency doubler

Abstract: A structure that consists of a λ/4 stepped-impedance microstrip resonator is proposed as an instrument for the investigation of nonlinear effects in thin magnetic films and also can be used as a microwave frequency doubler. A conversion efficiency of 0.65% is observed at a one-layer 100 nm Ni80Fe20 thin film at an input signal level of 4.6 W for a 1 GHz probe signal. The maximum measured conversion efficiency (1% at 1 GHz) was achieved for the 9-layer Ni80Fe20 film where 150 nm magnetic layers were separated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Such devices, based on ferrites, demonstrated competitive conversion factor at high input powers [15,17], although in the case of thin metallic magnetic films in coplanar or microstrip waveguides conversion factor was actually quite low [21,23]. However, it can be significantly increased if instead of the waveguide the microstrip resonator will be used [34]. As a final note, from the analysis of second harmonic generation power dependence, we have suggested that there were spin wave instability processes for the LF peak but not for the HF one, which is possibly related to the conditions of spin waves excitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such devices, based on ferrites, demonstrated competitive conversion factor at high input powers [15,17], although in the case of thin metallic magnetic films in coplanar or microstrip waveguides conversion factor was actually quite low [21,23]. However, it can be significantly increased if instead of the waveguide the microstrip resonator will be used [34]. As a final note, from the analysis of second harmonic generation power dependence, we have suggested that there were spin wave instability processes for the LF peak but not for the HF one, which is possibly related to the conditions of spin waves excitation.…”
Section: Discussionmentioning
confidence: 99%
“…After filtering by BPF2, the rf signal consisting only of the secondharmonic component reached the spectrum analyzer for measurements of its power. The filters used were of our design and fabrication [34].…”
Section: Measurement Setupmentioning
confidence: 99%